Design and fabrication of Compact Shredding Machine for onsite Composite center - Ananthi. K, N. Kousal, K. Naveenkumar, S. Athipathi, M. Murugan (International Journal of Advanced Science and Technology, 2020)
The main scope of the paper is to conceptually design and develop a shredding machine in compact size that focuses on the manufacture of dry leaves, areca leaves, chopped dry and worm compost. This concept was developed by considering four slicing machines having different operations and operating processes. The concept was developed by taking care of the safety factor for the customers. The machine consists of a three stage motor, bearings, cutter, structural frame, spur gear and dual shaft. The frame of the machine is built using high carbon steel used for making soft steel and cutter tip. Sixteen cutters are mounted on two shafts rotating parallel to the spur gear. The belt drive is responsible for the transmission of electric motor power to the cutter shaft. The cutting process inside the cutting house is due to the tensile and friction. The dried leaves are cut down and the chopped powder is collected in a bowl in the bottom. This design is compact and can be easily used.